2012
DOI: 10.1007/978-1-4614-4726-9_4
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile in Children: A Review of Existing and Recently Uncovered Evidence

Abstract: The clinical significance of the presence of Clostridium difficile in children's faeces remains uncertain using current diagnostic procedures. Clostridium difficile is a relatively common finding in infants with no symptoms of gastrointestinal disease, suggesting it may be an incidental finding and form part of the normal gut micro-flora in this age group. On the other hand, particularly in older children or those with significant co-morbidity, there are examples where C. difficile causes disease and exerts co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 92 publications
1
2
0
Order By: Relevance
“…In the youngest age categories, the occurrence in control subjects was comparable to that in case subjects, as were the differences in pathogen load. High numbers of C. difficile-positive detection in children without GI complaints are known [23], while asymptomatic carriership among the elderly seems much less frequent [24]. This correlates with our findings, which found decreasing relative load with age in control subjects together with increasing differences in pathogen load between case and control subjects with age (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In the youngest age categories, the occurrence in control subjects was comparable to that in case subjects, as were the differences in pathogen load. High numbers of C. difficile-positive detection in children without GI complaints are known [23], while asymptomatic carriership among the elderly seems much less frequent [24]. This correlates with our findings, which found decreasing relative load with age in control subjects together with increasing differences in pathogen load between case and control subjects with age (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Alongside a lack of clear CDI case definitions in those children under the age of 3 years [5], detection of C. difficile is commonly interpreted as asymptomatic colonisation and not the causative agent for diarrhoea. However, there have been reports of a potential pathogenic role of C. difficile in this patient population, as occurs in adults [4,6,7]. A recent study suggested that the use of adult markers of disease severity are not useful in guiding the management of CDI in children ≤16 years of age, which makes it difficult to design and interpret clinical studies [8].…”
Section: Introductionmentioning
confidence: 96%
“…C. difficile is a spore-forming, anaerobic, gram-positive bacillus bacterium which causes a wide spectrum of illnesses from asymptomatic colonization or mild diarrhea to fulminant disease characterized by toxic megacolon, sepsis, pseudomembranous colitis and death (2-4). C. difficile infection is less common in children than adults, but its prevalence is increasing in children (5-7). Disease is mainly occurred in children who have been treated with long term antibiotic therapy (8, 9).…”
Section: Introductionmentioning
confidence: 99%